Simulating the distributive effects of the Macron-Merkel-Recovery Fund - Friedrich Heinemann (ZEW - Leibniz Centre for European Economic Research, 2020)
In a joint initiative, the political leaders of France and Germany have proposed to set up a EUR 500 billion fund to support the recovery of the EU economy from the COVID-19 recession. The Recovery Fund (RF)shall be financed through the issuance of bonds by the European Commission. Repayments will be made from the EU budget. The money is to be used to support sectors and regions particularly affected by the negative economic consequences of the pandemic. This expertise sheds light on the direction and magnitude of the resulting net-payments through the Fund. It provides simulations on the spending and refinancing side.
Keywords: 330